Structure and dynamics in the nucleosome revealed by solid-state NMR - Shi, Xiangyan (2018)
Eukaryotic chromatin structure and dynamics play key roles in genomic regulation. In the current study, we implemented solid-state NMR (SSNMR) technique to investigate secondary structure and intramolecular dynamics of the nucleosome core particle (NCP) and nucleosome array at atomic level. Secondary structure elements are successfully localized in the human histone H4 in the NCP precipitated with Mg2+. In particular, dynamics on nanosecond to microsecond and microsecond to millisecond timescales are elucidated, revealing diverse internal motions in the histone H4 protein. The results suggest that the histone dynamics might contribute to the regulation of chromatin mobility and DNA accessibility. Furthermore, our study reveals that H4 in the nucleosome array adopts the same structure and show similar internal dynamics as that in the NCP assembly while exhibiting relatively restricted motions in several regions consisting of residues in the N-terminus, Loop 1 and the α3 helix region.